Evaluation of Guava (Psidium guajava L.) Varieties and Standardization of Recipe for Nectar Preparation - Madan Lal Choudhary (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2008)
The nectar prepared from guava variety L-49 had highest ascorbic acid, pH and non-reducing sugar. The recipe with 20 per cent pulp, 0.3 per cent acidity and 17°Brix (TSS) recorded highest organoleptic score. The acidity, TSS, total and reducing sugar of nectar showed an increasing trend during the progress of storage upto five months under ambient conditions. However, these chemical constituents did not change markedly until five months of storage as compared to fresh nectar at the time of preparation.